Implementasi Learning Star With A Question Sebagai Upaya Dalam Meningkatkan Aktivitas Pembelajaran Siswa Di Madrasah - Sudrajat, Husaen (Mataram University, 2024)
The purpose of this study was to determine the implementation of Learning Star With A Question as an effort to improve student learning activities in madrasah. This study is a classroom action research. The setting or location of the study is MI At-Tarbiyah Addiniyyah. The type of instrument used by researchers in collecting data in this study is an observation sheet consisting of data on teacher activity and student activity. Learning outcomes are seen from the tests given to students which are measured through classical provisions. The results of observations of student learning activities in the first cycle showed an average percentage of student activity of 55% with a fairly good category and an average teacher activity of 50% with a fairly good category, the number of students asking questions in the first cycle was 19 people with a percentage of 70%. The results of the second cycle of learning observations showed an average percentage of student learning activities of 85% with a very good category and an average percentage of teacher activities of 83% with a very good category. The number of students asking questions in the second cycle was 27 students with a percentage of 100%. The completeness of learning for the first cycle of students by 48% increased in the second cycle to 77%. From the results of research and discussion, it can be concluded that Learning Star With A Question implementation is one of the efforts that can be done in improving student learning activities in madrasah. The improvement can be seen from the score in each cycle.